Smartphone Use and its Effects on the Student Final Grade (a case study in the Environmental ChemistryClass) - Nazar, Muhammad; Muliana, Rahmi; Hanum, Latifah (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research aimed at investigating the effects of smartphone usage on the environmental chemistry studentâs final grades and identifying the dominant applications used by students in order to help the learning process during environmental chemistry course taking. The participants in this research were 24 students who enrolled the environmental chemistry course in the even semester of academic year 2017/2018. The duration of smartphone usage data was collected by using App Usage application, student responses were recorded using questionnaires and the final scoreobtained from the final test results. The result reveals that for every 1000 seconds increase of smartphone use yields an increase in a final score about 1 point (out of 100). In the other word, the independent variable can explain the dependent variable of about 16.4%. The app usage also recorded that some applications dominantly used by students in the environmental chemistry coursewere found to be browser application such as Chrome and MozillaFirefox, data processing application such as Microsoft Word, Microsoft Power Point and PDF Reader. This result implies that if the use of smartphone is properly controlled, the positive effects could be gained.